Human behaviour in informal settlement fires in Costa Rica. (October 2021) - Guevara Arce, Sara; Jeanneret, Chloe; Gales, John; Antonellis, Danielle; Vaiciulyte, Sandra
Highlights: Video footage of an informal settlement fire, showing fire and resident behaviours. Relationship between fire behaviour and firefighters' efforts to control events. Complex, highly situational social and environmental interactions are considered. Proposed methodology for analysis of informal settlement fires' behavioural data. Compilation base for human and fire behaviour in Costa-Rican informal settlements. Abstract: Globally, 1 billion people live in informal settlements, which are typically highly susceptible to fire. Small fires can quickly evolve into large conflagrations causing significant losses of life and property, injuries, and subsequent exacerbation of residents' existing vulnerabilities. Informal settlement fires are a complex socio-technical phenomenon which involve a combination of fire dynamics, structural and behavioural response. These fires are not broadly researched nor are they well understood. In this paper, the authors attempt to illustrate this multi-faceted issue and provide recommendations to help guide future research. Emphasis is placed on human behaviour in response to fires, including fire response activities by residents and city fire brigades. The case study presented in this paper is a 2019 fire which occurred in El Pochote, an informal settlement located in San José, the capital of Costa Rica. Through the Costa Rican Fire Corps, video footage recorded live and in-situ (70 min) of the brigades' and residents' actions in this event was obtained. This video shows real-time human behaviour and fire response activities, as well as complex fire dynamics and resulting structural reactions. It is clear from this footage that human behaviour responses to informal settlement fires are highly coupled with local context and specific situations, demonstrating limitations with extending observations from a specific case study to informal settlements more broadly. This paper introduces a methodology for situational analysis and documentation of human behaviour responses based on video footage of informal settlement fires. It provides key insights to how key stakeholders such as the Costa Rican Fire Corps, the police and informal settlement dwellers interact with each other and respond to fires in informal settlements in Costa Rica. These results form a first-stage contextualization of informal settlement fires in Costa Rica, which can be used to inform the Costa Rican Fire Corps, non-governmental organizations and other stakeholders that may be able to support fire safety improvements in Costa Rican informal settlements. Despite the challenging nature of studying human behaviour from real-life footage, the authors aim to establish a foundation for future research in compiling evidence of human behaviour in informal settlement fires across different countries.